Bioethanol Production from Steam-Pretreated Agricultural Residues of Cassava using Separate Hydrolysis and Fermentation (SHF) - Pooja, NS; Sajeev, MS; Jeeva, ML; Padmaja, G (JOURNAL OF ROOT CROPS, 2017)
Agricultural residues of cassava (Manihot esculenta Crantz) such as stems and peels contain high amount of starch in addition to cellulose, hemicelluloses and lignin and hence appropriate pretreatment and enzymatic hydrolysis strategies are to be designed for optimal fermentable sugar and ethanol yields. The potential of three steam-pretreated cassava residues (stems, leaves and peels) for bioethanol production was investigated by separate hydrolysis and fermentation (SHF). It was found that out of three enzyme cocktails such as Cellic+Stargen, Cellic+Stargen+Optimash XL and Cellic+Stargen+Optimash BG (C+S+OBG), the highest reducing sugar (RS) release was obtained from the latter system for all the residues. Maximum RS yield was obtained from cassava peels (66.43g l-1) followed by stems (32.18 g l-1) using the latter enzyme cocktail. Glucose was the predominant sugar present in the hydrolysates. Sugar consumption during fermentation (48 h) using Saccharomyces cerevisiae was also the highest for cassava peels (47.54 g l-1). The highest ethanol yield of 21.68 g l-1 was obtained from peels in C+S+OBG system, while the yields from stems and leaves were 12.92 and 6.17 g l-1 respectively. Although the highest fermentation efficiency of 91.59% was obtained from C+S+OBG saccharified stems, volumetric ethanol productivity and ethanol recovery were the highest from peels (0.452 g l-1 h-1 and 264.36 ml kg-1 dry biomass), while ethanol recovery was 157.52 and 75.24 ml kg-1 respectively from stems and leaves. The study showed that among the residues, cassava peels had the highest potential as feedstock for bioethanol production.